Barriers to integrating tourism in the development planning: The perspective of the Malaysia local authorities - Abdul Khalid, Siti Nabiha; Md Saad, Nor Hasliza; Mahadi, Rozaidy (2013)
This paper discusses the barriers faced by the local authorities in Malaysia in integrating tourism in their development planning. This study undertook a quantitative survey. The questionnaires were sending out to 99 local authorities in Peninsular of Malaysia and 50% respondent rate were obtained. The findings show that 49 percent of Malaysia’s local authorities have formulated policies related to tourism development in their area of jurisdiction. Financial restriction, which is high cost, has been identified as the major barrier for those LAs in integrating tourism in their development planning and policy formulation. The findings also revealed that time constraints and view that tourism activities as not being an important contributor to their revenue are among the factors that prevent them from integrating tourism in their development planning.